Enrichment of Anti Hoax Competency among Secondary School Students - Watumesa Agustina Tan; Theodorus Eko Pramudito (Institute for Research and Community Services, 2022)
Hoax and misinformation are common occurrences in the current era of social media. Nurturing critical thinking is necessary to combat the proliferation of hoaxes, especially in the younger generation. In this activity, we conducted a workshop for high school students and teachers to build awareness of hoaxes and how to identify them. This in-person workshop was held at Canisius College High School in a three-hour session. After taking part in the workshop, participants were expected to be able to explain the definition of a hoax, explain why hoaxes exist and are spread out among the community, and analyze the credibility of new information. For this purpose, the workshop consisted of three sessions. In the first session, the facilitators walked all participants through a lively discussion on what hoaxes are and how they get passed on from one person to another. In the second session, we introduced the concept of credibility to the participants. In the final session, the participants practiced evaluating the credibility of news. All sessions were delivered as paired or group discussions using authentic articles or postings from various social media platforms. The evaluation survey at the end of the activity showed that the participants agreed that the topic covered by this workshop was necessary and useful; however, they felt that the event was too short. This opportunity provided insights into how to improve similar hoax awareness-raising programs in the future.